Peningkatan Efisiensi Stasiun Kerja dengan Line Balancing di CV. Sinar Baja Electric - Laura Widjaja Laura Widjaja; Nova Sepadyati (Jurnal Titra, 2022)
CV. Sinar Baja Electric is a company that produces speakers. The speakers are made by assembling. Line balancing analysis aims to improve the work station efficiency and give some solution about devide the workload to some operators. The line balancing method used is Rank Positional Weight method. Line balancing will be success if there is an increase in line efficiency. It also can be success if there is a decrease in balance delay, idle time, and smoothes index. The result of calculation show that there is a reduction in the number of work stations and the number of operators, from 34 stations and 36 operators to 28 stations and 30 operators. The average line efficiency of all operations also increased from 63,71% to 75,34%. This suggestion can be made by using helper, do training, and adding tools.